STRUCTURE, PURPOSE AND TASKS OF THE VOLLEYBALL SECTION (International Conference on Medical Science, Medicine and Public Health, 2025)
The article examines in detail the goals, tasks, planning and implementation of the volleyball section in schools and other educational institutions. The structure of the volleyball sports section, including organizational and methodological parts, is described. The article provides detailed information on the structure of the volleyball sports section, highlighting the importance of each component to the successful operation and achievement of its goals.